Wounds May Heal, but Scars Remain: Conflict, Tragedy, and The Inherited Legacy of Trauma - Istanto, Alleta Antjani (JURNAL HISTORICA, 2024)
This writing explores the historical experiences of the author's family, particularly regarding the anti-Chinese racial conflicts endured by Kweek Hwie Bian, the maternal grandfather, who faced persecution during three different periods in Indonesia. The author reveals how violence and racial discrimination have shaped and erased part of the family's ethnic identity. From the exodus in Semarang in 1965 due to the PKI riots, to the conflicts in 1980-1981 and the May 1998 riots, this narrative highlights the inherited trauma and the family's efforts to maintain their existence. The name change from Kweek Hwie Bian to Soebianto reflects an extreme measure to avoid persecution. These stories demonstrate how the dark history of racial persecution affects subsequent generations, erasing cultural identity and instilling a deep-seated fear of expressing their ethnic identity in Indonesia.